Some Mixed Ligand Complexes of Tungsten Oxytetrachloride - Dabas, P.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Some mixed ligand derivatives of WOCl4 have been synthesized and characterized by their elemental analysis, IR and electronic spectra. The amide ligands are attached to tungsten atom within coordination sphere providing an octahedral geometry to the complex molecule. The amide ligand is removable by simple heating. The tungsten atom-phenoxy linkage is slowly ruptured by boiling in alcohol. This particular property has been utilised for the synthesis of mixed phenoxy complexes without amide ligands but with cyclopentadienide and indenide groups—a new way of synthesis of mixed phenoxy complexes containing π-bonded cyclopentadienyl and indenyl groups.